Making Out-of-School-Time Matter Evidence for an Action Agenda - Bodilly, Susan J. (RAND Corporation, 2005)
Presents the findings of a broad-ranging literature review intended to identify, frame, and assess relevant issues concerning effective out-of-school-time (OST) programs. Drawing on recent studies the authors identify and address the level of demand for OST services, the effectiveness of offerings, what constitutes quality in OST programs, how to encourage participation, and how to build further community capacity. They make recommendations for improving the information used in policy making.